Taxonomy of Eumenes punctatus-complex (Hymenoptera: Vespidae: Eumeninae) from Korea with DNA barcoding and key to Far Eastern species of the genus Eumenes Latreille, 1802 - Yoon, Tae Joong; Kim, Jeong-Kyu (Zootaxa, 2014)
Based on DNA barcoding analysis and morphological comparison, new synonymy is proposed for Eumenes punctatus de Saussure, 1852 =E. asioboreus Kim & Sk. Yamane, 2001, syn. nov. Independent status of the Far Eastern species E. rubrofemoratus Giordani Soika, 1941 from the transpalearctic E. coarctatus (Linnaeus, 1758) is supported, suggesting their recent origin with comparatively low genetic divergence. A revised key to the Far Eastern species of the genus Eumenes is provided. Distribution of E. quadratus Smith, 1852 is corrected and E. rubrofemoratus Giordani Soika, 1941 is newly recorded from South Korea. For future taxonomic comprehension of the Far Eastern Eumenes, problematic species pairs requiring additional molecular tests are hereby suggested and discussed.